Production of Pleurotus ostreatus var. Florida on briquettes and recycling its spent substrate as briquettes for fuel grade biosolids - Moreira, Bruno Rafael de Almeida [UNESP] (2020)
Development and implementation of strategies targeting downstream steps to convert spent mushroom substrate into energy or bioproducts are an urgent matter. This may ensure that edible mushrooms are both sustainable to cultivate and also are able to be competitive with conventional sources of proteins. Accordingly, this study aimed at developing an integrated system to firstly produce oyster mushroom on sugarcane bagasse shaped into briquettes, then, recycle its spent material into fuel grade biosolids. To make special briquettes for production of P. ostreatus var. florida, sugarcane bagasse, corn meal, wheat bran, and calcitic limestone at the ratio of 30: 2.5: 2.5: 1 m m−1 (dry matter) were placed together in polyethylene bags, water added to 40, 60 and 80% moisture, then, pressed at 15, 30, 45, and 60 MPa using a pilot-scale hydraulic piston presser. At the end of thirty days of axenic cultivation, the spent material was dried and milled, then, reconverted into briquettes at the standard-pressure of 120 MPa. Production briquettes of 45 MPa, with 60 and 80% moisture, had the greatest productivity of mushrooms, 28.30% and 30.40%, and generated the lowest quantities of spent substrate, 46.70% and 44.80%, respectively. The relative energy density in solid biofuels from recycling the highest producers was the lowest, 2865.40 MJ kg−3 and 2573.05 MJ kg−3, respectively. In conclusion, a complete system of cultivating P. ostreatus var. florida and producing briquettes was successfully developed. This concept technically was efficiency in converting lignocellulosic residues into high-performance substrates for protein-rich food production. As well, this recycled the spent mushroom substrates into medium-quality fuel grade biosolids.